СОЦІОЛОГІЯ ЗНАННЯ ТА НАУКИ В КОНТЕКСТІ ФІЛОСОФІЇ НАУКИ - Гейко, С. М. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
У статті висвітлюється процес формування соціології знання – концепції, яка досліджує соціальну зумовленість знання, по-новому інтерпретує знання, завдяки розширенню суб’єкта аж до суспільства в цілому. В ХХ столітті набуває стрімкого розвитку соціологія науки – галузь соціологічних досліджень, яка розглядає науку як соціальний інститут. С.Н. Гейко. Социология знания и науки в контексте философии науки. В статье освещается процесс формирования социологии знания – концепции, которая исследует социальную обусловленность знания, по-новому интерпретирует знание, благодаря расширению субъекта вплоть до общества в целом. В ХХ веке приобретает стремительное развитие социология науки – отрасль социологических исследований, которая рассматривает науку как социальный институт. Ключевые слова: наука, социология, социология знания, социология науки, научное сообщество. S. Geiko. Sociology of knowledge and science. The process of formation of sociology of knowledge as the concept which researches the social dependence of knowledge and makes new interpretation of knowledge due to extension of subject up to society as whole is highlighted at the article. The sociology of science as new branch of sociological researches reviewing science as social institute starts high speed development in XX century. Keywords: science, sociology, sociology of knowledge, sociology of science, scientific community.